Putting the Person Back in Person-Brands: Understanding and Managing the Two-Bodied Brand - Fournier, Susan; Eckhardt, Giana M. (Journal of Marketing Research, 2019)
This article provides insight into the management of brands that are also people by unpacking the interdependencies that exist between people and brands and focusing on the qualities that make person-brands human rather than on the qualities that make them brands. Using the extended case method to examine 20 years of public data about the Martha Stewart brand, the authors highlight the interdependent relationship between the person and the brand—in particular, consistency and balance—and identify four aspects of the person that can upset these interdependencies: mortality, hubris, unpredictability, and social embeddedness. Mortality and hubris can cause imbalance, but with the right skills and structures, these factors can be proactively managed. Inconsistency in the meanings of the person versus the brand can derive from the person’s unpredictability and social embeddedness and compromise brand value, but it may also enhance brand value by adding needed intimacy and authenticity. This two-bodied conceptualization suggests renewed management principles and contributes to branding theory through identification of the doppelgänger within, new brand strength facets, and emphasis on risk versus returns.